2021
DOI: 10.3390/jcm10194602
|View full text |Cite
|
Sign up to set email alerts
|

Self-Injuries and Their Functions with Respect to Suicide Risk in Adolescents with Conduct Disorder: Findings from a Path Analysis

Abstract: Non-suicidal self-injuries (NSSIs) have been identified as one of the most predictive factors of suicidal behaviours in adolescents. However, it remains unknown whether certain functions of NSSIs are associated with suicide risk, and what are the underlying mechanisms. Therefore, we aimed to investigate the association between functions of NSSIs and suicide risk in adolescents with conduct disorder (CD), which shares some common characteristics with NSSIs. Participants were 215 adolescents (155 females, 72.1%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…So far there is limited data about the association of venturesomeness with suicide-related outcomes. Previous studies have found no signi cant association between venturesomeness and suicidality in the population of pathological gamblers (53) and adolescents with conduct disorders (54), as well as no association with self-harming behaviors (55).…”
Section: Discussionmentioning
confidence: 77%
“…So far there is limited data about the association of venturesomeness with suicide-related outcomes. Previous studies have found no signi cant association between venturesomeness and suicidality in the population of pathological gamblers (53) and adolescents with conduct disorders (54), as well as no association with self-harming behaviors (55).…”
Section: Discussionmentioning
confidence: 77%